Decreased fertility rates in 9639 women diagnosed with inflammatory bowel disease: a United Kingdom population-based cohort study - Ban, Lu; Tata, Laila J.; Humes, David; Fiaschi, Linda; Card, Timothy R. (Wiley, 2015)
Background: Clinical studies have reported reduced fertility in women with inflammatory bowel disease (IBD).